EVALUASI PROGRAM KERJASAMA KOMPETENSI KEAHLIAN TEKNIK SEPEDA MOTOR DENGAN HONDA DI SMK MUHAMMADIYAH 1 SURAKARTA DENGAN MENGGUNAKAN MODEL CIPP - Iswanda Iswanda; Yuyun Estriyanto; Nyenyep Sriwardani (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
The purpose of this study is determine the collaboration of motorcycle engineering expertise competencies with Honda viewed from (1) aspects of the context which include; (a) the background of the cooperation program, (b) purpose, (c) objectives, and (d) relevance; (2) input aspects which include (a) curriculum, (b) HR, (c) financing, (d) facilities and infrastructure, (e) competency evaluation; (3) aspects of the process that includes; (a) learning programs,(b) apprenticeship, (c) teacher training, and (d) problems in the field; (4) product aspects which include; (a) opportunity to enter the workforce, (b) graduate competencies, (c) conformity to expectations.This study was used a evaluation method of the CIPP model (Context, Input, Process, and Product). The data sources came from 9 graduate of the TSM Honda Department students, the Head of the TSM Honda Department Program, the Head of the BKK, the TSM-Honda program development coordinator, and 13 Heads of AHASS workshops. The validation of the questionnaire items was used logical validity. The data analysis technique was uses description supported by the average analysis based on the assesment criteria.The results show that: (1) aspects of the context which consisted of four indicators, namely the background of the TSM-Honda program collaboration, purpose, objectives and relevance of the program had all been in conformity and there had been an MOU between the school and Honda. (2) input aspects have been carried out in accordance with agreed procedures; (a) the process of making curriculum involves both parties, (b) preparation of human resources for training, (c) financing of facilities and infrastructure and (d) preparation of facilities and infrastructure conducted by schools, and (e) evaluating student competencies. (3) aspects of the process have been carried out by each party well and in accordance with procedures. Which consists of (a) practice-based learning programs, (b) apprenticeship students in AHASS workshops, (c) teacher training and certification and (d) field problem can be solve. (4) aspects of the product consist of (a) opportunitiy to enter the workforce still needs to be improved (b) the application of competence is 72% and job satisfaction which reaches 77.8% shows a good scale. (c) graduated satisfaction after studying at TSM Honda shows a good scale at 80%.The purpose of this study is determine the collaboration of motorcycle engineering expertise competencies with Honda viewed from (1) aspects of the context which include; (a) the background of the cooperation program, (b) purpose, (c) objectives, and (d) relevance; (2) input aspects which include (a) curriculum, (b) HR, (c) financing, (d) facilities and infrastructure, (e) competency evaluation; (3) aspects of the process that includes; (a) learning programs,(b) apprenticeship, (c) teacher training, and (d) problems in the field; (4) product aspects which include; (a) opportunity to enter the workforce, (b) graduate competencies, (c) conformity to expectations.This study was used a evaluation method of the CIPP model (Context, Input, Process, and Product). The data sources came from 9 graduate of the TSM Honda Department students, the Head of the TSM Honda Department Program, the Head of the BKK, the TSM-Honda program development coordinator, and 13 Heads of AHASS workshops. The validation of the questionnaire items was used logical validity. The data analysis technique was uses description supported by the average analysis based on the assesment criteria.The results show that: (1) aspects of the context which consisted of four indicators, namely the background of the TSM-Honda program collaboration, purpose, objectives and relevance of the program had all been in conformity and there had been an MOU between the school and Honda. (2) input aspects have been carried out in accordance with agreed procedures; (a) the process of making curriculum involves both parties, (b) preparation of human resources for training, (c) financing of facilities and infrastructure and (d) preparation of facilities and infrastructure conducted by schools, and (e) evaluating student competencies. (3) aspects of the process have been carried out by each party well and in accordance with procedures. Which consists of (a) practice-based learning programs, (b) apprenticeship students in AHASS workshops, (c) teacher training and certification and (d) field problem can be solve. (4) aspects of the product consist of (a) opportunitiy to enter the workforce still needs to be improved (b) the application of competence is 72% and job satisfaction which reaches 77.8% shows a good scale. (c) graduated satisfaction after studying at TSM Honda shows a good scale at 80%.